Pengaruh Permainan Truth Or Dare Dalam Pembelajaran PAI Di Kelas VII & VIII SMPN 1 Bukittinggi - Ahmad Rijal Sabili; Fenny Ayu Monia; Zulkifli Zulkifli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This Field Experience Practice (PPL) aims to gain experience related to teacher studies, in order to fulfill one of the subjects of the Islamic Religious Education Bachelor's program at the State Islamic University of Sjech Djamil Djambek Bukittinggi and provide students with knowledge and even experience in the world of education. Regarding an educational process which was implemented at SMP 01 BUKITTINGGI as an effort to increase learning in terms of students' interest in participating in the learning process, so in this case the time ranges more or less between 28 August - 01 November 2023 which followed the independent curriculum-based learning process at SMP 01 BUKITTINGGI In implementation The educational program carried out in grades 7 and 8 uses the truth or dare game learning system within the scope of Islamic Religious Education. The implementation starts from the approach, explanation of material, direction and implementation of the learning system which is carried out in accordance with the truth or dare system that has been designed. Field Experience Practice (PPL) is carried out at SMP 01 BUKITTINGGI which is located at Jl. Sudirmn, Kota Bukittinggi, Prov. West Sumatra. In its application, results are obtained in the development of learning that has variety and innovation and allows students to increase their focus and increase their intellectual value in learning.